SK4 K+ channels are therapeutic targets for the treatment of cardiac arrhythmias - Shiraz Haron‐Khun; David Weisbrod; Hanna Bueno; Dor Yadin; Joachim Behar; Asher Peretz; Ofer Binah; Edith Hochhauser; Michael Eldar; Yael Yaniv; Michael Arad; Bernard Attali (EMBO Molecular Medicine)
Abstract Catecholaminergic polymorphic ventricular tachycardia (CPVT) is a stress‐provoked ventricular arrhythmia, which also manifests sinoatrial node (SAN) dysfunction. We recently showed that SK4 calcium‐activated potassium channels are important for automaticity of cardiomyocytes derived from human embryonic stem cells. Here SK4 channels were identified in human induced pluripotent stem cell‐derived cardiomyocytes (hiPSC‐CMs) from healthy and CPVT2 patients bearing a mutation in calsequestrin 2 (CASQ2‐D307H) and in SAN cells from WT and CASQ2‐D307H knock‐in (KI) mice. TRAM‐34, a selective blocker of SK4 channels, prominently reduced delayed afterdepolarizations and arrhythmic Ca2+ transients observed following application of the β‐adrenergic agonist isoproterenol in CPVT2‐derived hiPSC‐CMs and in SAN cells from KI mice. Strikingly, in vivo ECG recording showed that intraperitoneal injection of the SK4 channel blockers, TRAM‐34 or clotrimazole, greatly reduced the arrhythmic features of CASQ2‐D307H KI and CASQ2 knockout mice at rest and following exercise. This work demonstrates the critical role of SK4 Ca2+‐activated K+ channels in adult pacemaker function, making them promising therapeutic targets for the treatment of cardiac ventricular arrhythmias such as CPVT.